Contrast-ultrasound dispersion imaging for renal cell carcinoma diagnostics - Chen, Peiran; Turco, Simona; Liu, Zhaohan; Widdershoven, Christiaan; Oddens, Jorg; Wijkstra, Hessel; Mischi, Massimo; Zondervan, Patricia (The Ultrasound Journal, 2025)
Cost-effective screening methods for Renal Cell Carcinoma (RCC) are still lacking. Angiogenesis is a recognized hallmark of cancer growth, leading to distinguishable perfusion patterns in tumors from those in normal tissue. This establishes the basis for diagnostic imaging solutions by dynamic contrast-enhanced ultrasound (DCE-US). In the past years, we have developed contrast-ultrasound dispersion imaging (CUDI) techniques to quantify prostate DCE-US acquisitions, obtaining promising results for prostate cancer localization. In this pilot study, we investigated for the first time its feasibility for RCC localization. DCE-US acquisitions of the kidney in 5 patients were used to perform CUDI analysis. With the obtained CUDI parameters and the delineated tumor and parenchyma regions, we performed pixel-based classification, from which the highest area under the receiver-operating-characteristic curve (AUC) = 0.96 was obtained for an individual patient, and an average AUC = 0.68 was obtained for the full patient dataset, showing the potential of CUDI for solid RCC localization. Further validation in a larger dataset and evaluation of the compatibility of point-of-care diagnosis are required.